The Trust Of Non-Wage Workers As A Determinant Of JKN Participation - Anggi Ardhiasti; Eko Rahman Setiawan (Universitas Pahlawan Tuanku Tambusai, 2023)
Background: The National Health Insurance (Jaminan Kesehatan Nasional/JKN) uses a social insurance mechanism whose participation is mandatory and relies its financing from participant contributions. In JKN participation, informal workers are included in the segment of Non-Wage Earners (Pekerja Bukan Penerima Upah/PBPU) which is still a challenge in increasing their participation to achieve universal health coverage. Aims: To analyze the relationship between trust of PBPU towards participation of JKN. Methods: A Quantitative study using a cross-sectional approach. A total of 369 samples of PBPU in Malang were collected with purposive and proportional sampling. The data were collected through a questionnaire and were analyzed using chi-square test and logistic regression analysis. Results: There was a significant association between trust toward BPJS Kesehatan, FKTP, and FKRTL as health service providers for the JKN program and PBPU's participation in JKN p = 0 (<0.05). PBPU, which has low trust in BPJS Kesehatan, FKTP, and FKRTL, has a higher tendency not to participate in JKN than PBPU which has high trust (OR 2.76 95% CI 1.65 – 4.60 each; OR 5.69 95% CI 2.27 – 14.25; OR 5.29 95% CI 2.22 – 12.62). Conclusion: Trust in JKN’s health care providers has a significant relationship to PBPU's participation in the JKN program. Thus, it is highly recommended to BPJS Kesehatan to always evaluate the performance of health service providers in collaboration with BPJS Kesehatan as one of the efforts to accelerate universal health coverage.